2015
DOI: 10.1371/journal.pone.0144595
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Filtration Bleb and Endplate Positioning Using Magnetic Resonance Imaging in Eyes Implanted with Long-Tube Glaucoma Drainage Devices

Abstract: BackgroundTo evaluate ocular fluid filtration and endplate positioning in glaucomatous eyes with long-tube glaucoma drainage devices (GDDs) using magnetic resonance imaging (MRI) and the effects of various factors on postoperative intraocular pressure (IOP).MethodsThis observational case series included 27 consecutive glaucomatous eyes (18 men, 7 women; mean age ± standard error, 63.0±2.0 years) who underwent GDD implantation (n = 8 Ahmed Glaucoma Valves [AGV] and n = 19 Baerveldt Glaucoma Implants [BGI]). Tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 43 publications
1
27
0
Order By: Relevance
“…These previous case series have demonstrated that filtering bleb volume is negatively correlated with postoperative IOP 7 , 8 . However, one study included eight cases with Ahmed glaucoma valve and Molteno implants 7 , whereas another study included 27 cases with Ahmed glaucoma valve and Baerveldt glaucoma implant with a 350-mm 2 or 250-mm 2 endplate 8 . IOP-lowering effect of these implants is affected by the size 9 11 , material 12 , and internal valve of the endplate 10 , 11 .…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…These previous case series have demonstrated that filtering bleb volume is negatively correlated with postoperative IOP 7 , 8 . However, one study included eight cases with Ahmed glaucoma valve and Molteno implants 7 , whereas another study included 27 cases with Ahmed glaucoma valve and Baerveldt glaucoma implant with a 350-mm 2 or 250-mm 2 endplate 8 . IOP-lowering effect of these implants is affected by the size 9 11 , material 12 , and internal valve of the endplate 10 , 11 .…”
Section: Introductionmentioning
confidence: 89%
“…High-resolution orbital images were obtained using a 3 Tesla scanner (Discovery MR 750 3.0 T; GE Healthcare, Milwaukee, WI) in combination with a 32-element phased-array head coil with fast imaging sequences employing steady-state acquisition cycled phases (FIESTA-C). The imaging parameters were as follows: repetition time, 5.6 ms; echo time, 2.7 ms; field-of-view, 180 mm; matrix size, 320 × 288; and a slice thickness of 0.6 mm with an overlap thickness of 0.3 mm, resulting in an in-plane resolution of 0.56 mm × 0.63 mm 8 . Images of the coronal plane were obtained perpendicular to the plane containing both optic nerves.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations